FUNCTIONS OF SINGING RESONATORS IN THEORY AND PRACTICE OF VOCAL LEARNING - Каплюк, А. С.; Василенко, Л. М. (SWorldJournal, 2022)
The article analyzes the resonant theory of singing. The functions of voice resonators are presented for consideration - energy, generating, phonetic, protective, indicator, activating, aesthetic and their essence is concretized